“Моїми словами руководить бажаннє захистити земську справу..” (лист професора Костя Мацієвича до гетьмана Павла Скоропадського, вересень 1918 р.) - Пиріг, Р. (Архіви України, 2009)
There is a review of the little-known document connected with the Law “About elections of provincial and povit (district) self-government members” adoption (May, 1918) in the publication. Also it includes a cursory description of K. Matsievych life.